KEJAHATAN ELEKTRONIK DENGAN PEMASANGAN SKIMER PADA SISTEM TRANSAKSI MESIN ATM - Kartini, Murtiningsih (Universitas Wiralodra, 2022)
The pace of improvement in internet technology will not only have a positive impact, but negative things will also appear as side effects including skimming crimes which are included in the form of cybercrime. Skimmer crime with the mode of installing tools on ATMs as a form of cybercrime crime and legal steps in overcoming the Crime of using information systems and electronic transactions. Through primary and secondary data developed and analyzed and reviewing Law Number 11 of 2008 and Law Number 16 of 2019 concerning Electronic Information and Transaction where it is known that the mode of operation of ATM electronic crimes as a form of cybercrime and the application of electronic information and transaction laws as an effort to overcome the crime of using information systems and electronic transactions.